Quercus purhepecha (Fagaceae), a new species of shrub oak endemic to the state of Michoacán, Mexico - Luna-Bonilla, Oscar Angel De; González-Rodríguez, Antonio; Rodríguez-Correa, Hernando; Piña-Torres, Javier; Coombes, Allen J.; Valencia-A., Susana (Phytotaxa, 2024)
Within the genus Quercus there are species with a shrubby habit that have been little studied worldwide. In Mexico, several shrub species within section Quercus are taxonomically highly problematic. These include eight named taxa that share traits such as abaxially tomentose leaves and growth of stems from one or multiple rhizomes, and there is evidence of additional undescribed species. Here, Quercus purhepecha is described and illustrated as a new tomentose shrubby white oak species, with a very restricted distribution within the Cuitzeo basin in the Trans-Mexican Volcanic Belt (TMVB), Michoacán state, Mexico. This new species is morphologically compared with Q. frutex, Q. microphylla and Q. repanda, which are similar taxa also distributed in the TMVB. In addition, a potential distribution model of Q. purhepecha for the Cuitzeo basin is presented.